In utero exposure to endocrine disrupting chemicals, micro-RNA profiles, and fetal growth: a pilot study protocol - Tricia L. Larose; Pål Sætrom; Marit P. Martinussen; Håkon Skogseth; Torkjel M. Sandanger; Ghislaine Scelo; Cliona M. McHale; Geir W. Jacobsen; Martyn T. Smith (SAGE Publishing, 2019)
Background: The developing fetus is particularly vulnerable to the effects of endocrine disrupting chemicals (EDCs). Molecular fingerprints of EDCs can be identified via microRNA (miRNA) expression profiles and may be etiologically implicated in the developmental origin of disease (DOHaD). Methods/design: This pilot study includes pregnant women at high risk (smoking at conception), and low risk (non-smoking at conception) for SGA birth (birthweight<10th percentile for gestational age). We have randomly selected 12 mothers (3 high-risk SGA birth, 3 low-risk SGA birth, 3 high-risk non-SGA birth, 3 low-risk non-SGA birth), with EDC measurements from gestational week 17. All offspring are female. We aim to test the stability of our samples (maternal serum, cord blood, placenta tissue), observe the differential expression of miRNA profiles over time (gestational weeks 17, 25, 33, 37, birth), and study the consistency between maternal EDC measures and miRNA expression profiles across our repeated measures. Expected impact of the study for Public Health: Results from this pilot study will inform the development of a larger cohort wide analysis, and will impact the current state of knowledge in the fields of public health, epigenetics, and the DOHaD.